On-Line performance records database for athletics - Kuntze, G.; Cheng, L.; Austin, T.; Nguyen, D.; Karla, D.; Kerwin, D. G.; Hailes, S.; Wilson, A. (Sportinformatik trifft Sporttechnologie. 8. Symposium der dvs-Sektion Sportinformatik in Kooperation mit der Deutschen Interdisziplinären Vereinigung für Sporttechnologie vom 15.-17. Dezember 2010 in Darmstadt, 2011)
Technology-assisted performance monitoring affords novel opportunities for tracking and guiding training programs and the development of elite as well as recreational athletes. Comprehensive training diaries are kept by athletes and coaches and coaching records are forming a prerequisite for funding allocation by for example, track and field athletics in the United Kingdom (uk sport, 2009). Sprinting is a highly technical discipline involving a multitude of strength, conditioning and technical training exercises and a significant number of parameters that may be recorded for athlete monitoring. The task of longitudinal record keeping becomes ever more complex and time-consuming and automation of this process, currently witnessed for example in the medical field, is a useful tool for managing data and relieving the coach and athlete from some record keeping tasks. As part of the SESAME project (Sensing for Sport and Managed Exercise, http://www.sesame.ucl.ac.uk/) an integrated system has been developed with the aim of providing fine grained performance information for the coach and athlete, for example split time, step frequency, step length, foot contact time, etc. A series of interviews with leading sprints coaches (Thompson, Bezodis, & Jones, 2009) revealed the importance of accurate and sport specific performance data, where longitudinal records may provide reliable assessments of athlete development, using specific historical points of reference, and allow for self-assessment of coaching practices as a means of quality control. Therefore, performance monitoring may be viewed as both a real-time and long term exercise.